2015
DOI: 10.1109/tnet.2014.2304439
|View full text |Cite
|
Sign up to set email alerts
|

Whispers in the Hyper-Space: High-Bandwidth and Reliable Covert Channel Attacks Inside the Cloud

Abstract: Abstract-Privacy and information security in general are major concerns that impede enterprise adaptation of shared or public cloud computing. Specifically, the concern of virtual machine (VM) physical co-residency stems from the threat that hostile tenants can leverage various forms of side channels (such as cache covert channels) to exfiltrate sensitive information of victims on the same physical system. However, on virtualized x86 systems, covert channel attacks have not yet proven to be practical, and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
201
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(203 citation statements)
references
References 17 publications
(34 reference statements)
2
201
0
Order By: Relevance
“…[48] showed that constructing a cross-VM side-channel is possible in Amazon's EC2, prompting further research on virtual machine infrastructure. Wu et al [49] use the EC2 as a host for covert communication. Exploiting peculiarities of the underlying x86 platform, they were able to achieve transmission rates of up to 100 bits/s.…”
Section: L4linux Resultsmentioning
confidence: 99%
“…[48] showed that constructing a cross-VM side-channel is possible in Amazon's EC2, prompting further research on virtual machine infrastructure. Wu et al [49] use the EC2 as a host for covert communication. Exploiting peculiarities of the underlying x86 platform, they were able to achieve transmission rates of up to 100 bits/s.…”
Section: L4linux Resultsmentioning
confidence: 99%
“…The application layer includes host-based attacks such as spamming, race condition attacks, buffer overflow attacks, mail forgery, and man-inthe-middle attacks. Host-based attacks are mostly attacks against system availability, operating systems performance, and web service operations [11]. Network-based incidents include attacks on networks aimed at affecting network availability and performance.…”
Section: Types Of Intrusionmentioning
confidence: 99%
“…Cloud Server is used for storing all the data and will also act as offline storage. All the data in the encrypted format will be stored at the cloud [25][26][27][28][29][30].…”
Section: Cloud Servermentioning
confidence: 99%